Widespread Occurrence of Self-Cleaving Ribozymes - Webb, Chiu-Ho T. (2009)
Hepatitis delta virus (HDV) and cytoplasmic polyadenylation element-binding protein 3 (CPEB3) ribozymes form a family of self-cleaving RNAs characterized by a conserved nested double-pseudoknot and minimal sequence conservation. Secondary structure-based searches were used to identify sequences capable of forming this fold, and their self-cleavage activity was confirmed in vitro. Active sequences were uncovered in several marine organisms, two nematodes, an arthropod, a bacterium, and an insect virus, often in multiple sequence families and copies. Sequence searches based on identified ribozymes showed that plants, fungi, and a unicellular eukaryote also harbor the ribozymes. In Anopheles gambiae, the ribozymes were found differentially expressed and self-cleaved at basic developmental stages. Our results indicate that HDV-like ribozymes are abundant in nature and suggest that self-cleaving RNAs may play a variety of biological roles.